1989
DOI: 10.1017/s0016672300028135
|View full text |Cite
|
Sign up to set email alerts
|

Genome size variation in the North American sunfish genusLepomis(Pisces: Centrarchidae)

Abstract: Genome sizes (nuclear DNA contents) were documented spectrophotometrically from individuals of each of nine species of the North American centrarchid (sunfish) genus Lepomis. The distributions of DNA values within and among the nine species were essentially normal and continuous, suggesting that changes in DNA quantity in Lepomis are small in amount, involve both gains and losses of DNA, and are cumulative and independent in effect. Significant differences in mean genome size were found between individuals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
2
18
1
Order By: Relevance
“…The intraspecific variation in genome size (2.97%) for this species is lower than the variation reported for other species of fish, such as the mean of 4.86% reported for 49 species of cyprinids (Gold et al 1990); the mean of 4.7% reported for 12 species of salmonids (Johnson et al 1987); and the mean of 6.24% reported for nine species of centrarchids (Ragland and Gold 1989). Demas et al (1990) identified male-specific Bkm fragments in the sea turtles Lepidochelys kempi and Chelonia mydas and female-specific fragments in C. mydas.…”
Section: Flow Cytometrycontrasting
confidence: 60%
“…The intraspecific variation in genome size (2.97%) for this species is lower than the variation reported for other species of fish, such as the mean of 4.86% reported for 49 species of cyprinids (Gold et al 1990); the mean of 4.7% reported for 12 species of salmonids (Johnson et al 1987); and the mean of 6.24% reported for nine species of centrarchids (Ragland and Gold 1989). Demas et al (1990) identified male-specific Bkm fragments in the sea turtles Lepidochelys kempi and Chelonia mydas and female-specific fragments in C. mydas.…”
Section: Flow Cytometrycontrasting
confidence: 60%
“…Although it is a common belief that the nuclear DNA content is constant within a species or that any variation would be negligible (Hinegardner 1968;Olmo 1983;CavalierSmith 1985), several recent papers have claimed the existence and pointed to the importance of intraspecific variations in both plants (Price at al. 1980;Laurie and Bennet 1985) and animals (Rao and Rai 1987;Gold and Amemiya 1987;Ferrari and Rai 1989;Ragland and Gold 1989;Alvarez-Fuster et al 1991;Lockwood et al 1991;Lockwood and Derr 1992;Ruedas et al 1993), that are presumably caused by gains or losses in various classes of DNA, including satellite DNA.…”
mentioning
confidence: 99%
“…This hypothesis is based on the assumption that the variation follows the premises of the normal probability density function (Sokal and Rohlf, 1969). An identical pattern of variation also occurs among populations of 9 species of the North American centrarchid genus Leporrcis (Ragland and Gold, 1989). Of importance is that no instance of a quantum or &dquo;quantized&dquo; (Cavalier-Smith, 1985b) (Price et al, 1981(Price et al, , 1986 (Gold and Price, 1985), both the normality of distributions within cyprinid populations and the apparent constraints on the quantity of DNA which can vary strongly imply the action of stabilizing or normalizing selection operating through the truncation of deleterious extremes (Stebbins, 1966;Mettler and Gregg, 1969).…”
Section: Discussionmentioning
confidence: 67%
“…A point to note, however, is that the evidence is essentially correlative and it would be difficult to determine experimentally whether the correlation was one of cause and effect or one of association. Moreover, intraspecific variation in genome size in both cyprinids and centrarchids can often be as great as the differences among species (Gold and Amemyia, 1987;Ragland and Gold, 1989;this On the other hand, the finding that ratios of mean genome size distance and variance in the Notropis versus Lepomis comparison differ markedly from those reported for structural genes and morphology suggests that different levels of the genome may follow independent evolutionary paths. The simplest explanation for the difference in distance and variance ratios is that genome size evolution is dependent, in part, on speciation episodes, whereas structural gene and morphological evolution are dependent primarily on elapsed time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation